Ezza Ezekuna New Yam Festival (Oke Aku) and its Impact on the Colonial Economy of Ebonyi State - Ongele, Festus Nwankwo; Anyigor, Judemary Ikechukwu (dialektika kontemporer, 2025)
The study is anchored on Cultural Capital Theory. The theory as developed by Pierre Bourdieu is of the view that cultural events and practices could be convertible into economic capital, generating values and profit. Using qualitative and content analyses Ezza Ezekuna New Yam Festival (Oke Aku) and its Impact on the Colonial Economy of Ebonyi State are examined. This discourse is supported by a primary source material, oral interview, and secondary sources, such as books and journal articles. The research investigated the relationship between the festival and the economy of Ezza and the state at large. It consciously interrogated how the colonial regime influenced the festival and the festival’s influence on the economy. It further examined the place of the festival in socio-cultural preservations, community practices, and political activities. Close observation revealed that the festival defiantly persisted under colonialism, and contributed to the local economy through stimulation of agricultural production, increasing sales, and promotion of cultural heritage which attracted people from different parts of Ebonyi State and beyond. It is further discovered that the festival encouraged community cohesion, profit maximization and income generation. It provided insights for policy makers, cultural administrators, and stakeholders seeking to leverage cultural festival for economic growth and transformation in the area.